MicroRNAs Importance: Defining the Importance Score of Human MicroRNAs and Their Single Nucleotide Mutants Using Random Forest Regression and Sequence Data (Adv. Theory Simul. 9/2019). Issue 9 (5th September 2019) - Cui, Chunmei; Shi, Bing; Shi, Jiangcheng; Zhou, Yuan; Cui, Qinghua
Abstract : In article number1900083, Chunmei Cui, Qinghua Cui, and co‐workers design a 'computational model', MIC, to quantify miRNA essentiality and identify the important ones from a huge number of miRNAs in human genome using miRNA sequence information. For the cover figure, the MIC model is like a superman (or archmage/magician) who can precisely select the miRNAs he/she needs from a huge number of miRNAs in the ball.